Do you imply:

(x^2 8x 4) / (x^2 x 6)

= (x^2 8x 4) / (x^2 2x 3x 6)

= (x^2 8x 4) / (x(x 2) 3(x 2))

= (x^2 8x 4) / ((x 3)(x 2))

Discontinuities at x = 3 and x = 2

(x^2 8x 4) / (x^2 x 6)

Issue the underside.

(x^2 8x 4) / ( (x 3) (x 2) )

Set the underside equal to zero.

x 3 = 0 x = 3

x 2 = 0 x = -2

Affirm the x values dont trigger the highest to be zero (it could then be a gap, nonetheless a discontinuity, however not a asymptote).

(-2)^2 8 (-2) 4 = -8

(3)^2 8(3) 4 = 37

Neither accomplish that x = -2, 3 are each vertical asymptotes, aka discontinuities.

This post is last updated on hrtanswers.com at Date : 1st of September – 2022